Acute Renal Failure in Systemic Lupus Erythematosus - Ponticelli, C. (1974)
Acute anuric renal failure complicating systemic lupus erythematosus does not usually respond to treatment with corticosteroids and immunosuppressive agents. We describe four cases treated by dialysis, corticosteroids, and heparin in anticoagulant doses in which there was remarkable improvement in renal function after prolonged anuria. One patient died later from a gastric haemorrhage. The other three were alive and well 55, 54, and 30 months from the onset of anuria. In two cases a second renal biopsy showed a striking improvement in the lesions. Large doses of corticosteroid and heparin may be the best treatment in acute anuric lupus nephritis.